Development and psychometric properties of the sexual and gender minority adverse childhood experiences (SGM-ACEs): Effect on sexual and gender minority adult mental health. (May 2022) - Schnarrs, Phillip W.; Stone, Amy L.; Bond, Mark A.; Salcido, Robert; Dorri, Armin A.; Nemeroff, Charles B.
Abstract: Background: Research has consistently shown a relationship between adverse childhood experiences (ACEs) and poor mental health outcomes, and recent research shows that sexual and gender minority (SGM) individuals are at increased risk for ACEs. Moreover, SGM individuals may experience unique ACEs. Increased risk for exposure to traditional and SGM-specific ACEs are related to heterosexism. Objective: The purpose of this paper is two-fold. First, establish the need for an SGM specific ACEs framework that accounts for exposure to heterosexism. Second, assess the psychometric properties of the SGM-ACEs scale. Participants and Setting: Data were collected using a multifaceted sampling strategy. In total, 1725 self-identified SGM Texans completed an online survey about ACEs, SGM-ACEs, mental health diagnoses, and demographic characteristics. Results: The most commonly reported SGM-ACEs were seeing or hearing of other SGM being physical harmed (71.2%), being bullied in school for being SGM (67.9%), and hearing religious leaders say homophobic, biphobic, or transphobic things (60.8%). The EFA showed that 7-items loaded onto a single factor and the CFA indicated a good model fit, with items showing a significant factor loading higher than 0.60. SGM-ACE showed adequate to good psychometric properties and predicted depression (AOR = 1.49, CI = 1.20, 1.86), anxiety (AOR = 1.61, CI = 1.25, 2.00), and PTSD (AOR = 1.97, CI = 1.47, 2.66), when controlling for ACEs and demographic factors. Conclusions: The 7-item SGM-ACEs measure is a psychometrically sound and unidimensional measure that can be quickly used to assess common adverse childhood experiences related to heterosexism.